Photodynamic therapy for actinic keratosis of the forehead and scalp: a randomized, controlled, phase II clinical study evaluating the noninferiority of a new protocol involving irradiation with a light‐emitting, fabric‐based device (the Flexitheralight protocol) compared with the conventional protocol involving irradiation with the Aktilite CL 128 lamp. (1st April 2019) - Vicentini, C.; Vignion‐Dewalle, A.S.; Thecua, E.; Lecomte, F.; Maire, C.; Deleporte, P.; Béhal, H.; Kerob, D.; Duhamel, A.; Mordon, S.; Mortier, L.
Summary: Background: Photodynamic therapy (PDT) is an effective treatment for actinic keratosis (AK), particularly for patients with large areas of field cancerization. Among the approved protocols in Europe, the most widely used requires irradiation with the Aktilite CL 128 lamp. However, pain during irradiation and the suboptimal adaptability of the lamp relative to the treatment area are two limiting factors of this protocol. To overcome these limits, a new protocol (referred to as the Flexitheralight protocol) involving irradiation with a light‐emitting, fabric‐based device was developed. Objectives: This paper aims to assess the noninferiority, in terms of PDT efficacy for treating AK, of the Flexitheralight protocol compared with the conventional protocol, which requires irradiation with the Aktilite CL 128 lamp. Methods: A monocentric, randomized, controlled, phase II clinical study was performed. Twenty‐five patients with grade I–II AKs of the forehead and scalp were treated with methyl aminolaevulinate PDT in two symmetrical areas. One area was treated with the conventional protocol ( n = 154 AKs), whereas the other area was treated with the Flexitheralight protocol ( n = 156 AKs). The primary end‐point was the lesion complete response (CR) rate at 3 months (an absolute noninferiority margin of –10% was used). The secondary end‐points included patient‐reported pain at the end of the irradiation. Results: At 3 months, the lesion CR rate with the Flexitheralight protocol was noninferior to that obtained with the conventional protocol (66·0% vs. 59·1%, respectively; absolute difference, 6·9%; 95% confidence interval –0·6% to 14·5%). Patient‐reported pain was significantly lower with the Flexitheralight protocol than with the conventional protocol (mean ± SD: 0·4 ± 0·6 vs. 5·0 ± 2·6; P < 0·0001). Conclusions: The Flexitheralight protocol is noninferior in terms of efficacy and superior in terms of tolerability to the conventional protocol for treating AKs of the forehead and scalp.